2019
DOI: 10.1177/0198742919876656
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development on Data-Based Individualization: A Mixed Research Study

Abstract: Data-based individualization (DBI) is a process of collecting and analyzing data on students’ response to intervention and then making intervention adaptations accordingly. Although this process can lead to better student outcomes, very few teachers are trained in the components of DBI, particularly in relation to behavior. Improving practice requires not only ongoing professional development, but also understanding about how teachers’ experiences in training can lead to better outcomes. Within the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…This would require professional development on how to collect reliable data and make data-informed decisions about phase changes, as teacher preparation programs generally do not provide practical experience in data-based decision-making (Majeika et al, in review). This type of training could be done in a series of sessions where teachers get hands-on experience collecting data, implementing intervention, and making data-based decisions alongside experts who provide on-going support (Bruhn et al, 2019 ). Providing this level of training could help practitioners as they grow in their knowledge, experience, and self-efficacy with data, and eventually, move this intervention from efficacious to effective (Hoagwood et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…This would require professional development on how to collect reliable data and make data-informed decisions about phase changes, as teacher preparation programs generally do not provide practical experience in data-based decision-making (Majeika et al, in review). This type of training could be done in a series of sessions where teachers get hands-on experience collecting data, implementing intervention, and making data-based decisions alongside experts who provide on-going support (Bruhn et al, 2019 ). Providing this level of training could help practitioners as they grow in their knowledge, experience, and self-efficacy with data, and eventually, move this intervention from efficacious to effective (Hoagwood et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the second research report in this series of examples, Bruhn et al (this special issue) used a convergent parallel MMR design to examine the usability and feasibility of ongoing professional development on teachers’ perceptions of self-efficacy using data-based individualization. In this study, qualitative and quantitative data were collected concurrently but analyzed separately for 16 participating general and special education teachers.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Taken together, these reviews may indicate researchers and practitioners are making a more concerted effort on the front end of intervention design to increase the likelihood of success. Furthermore, effectively adapting Tier 2 interventions can affect intervention acceptability, as research has demonstrated interventions are viewed favorably when they result in improved student behavior (Bruhn, Estrapala, et al, 2019). In the future, understanding the cost-effectiveness of implementing and adapting multiple Tier 2 interventions is necessary for better informing schools’ use of resources (e.g., adding or creating instructional materials, time spent implementing Tier 2 intervention, time away from academic instruction for students).…”
Section: Tier 2 Practicesmentioning
confidence: 99%